The Influence Of Job Satisfaction And Job Insecurity On Turnover Intention In Cleaning Labor And Dehasen University Security Workers - Susanto, Bogi; Fitriano, Yun; Harwini , Dewi (Universitas Dehasen Bengkulu, 2024)
Performance is basically related to the actions taken by employees and is influenced by the personality they have, performance also refers to behavior and activities as a whole that will support the achievement of company goals, the operational definition is a research dimension that provides data for researchers to find out how methods measure or assessing the variable Operational definition of the variable, based on the results of data analysis and hypothesis testing that has been done, the conclusions in this study are: performance satisfaction has an influence on Turnover Intention, Job Insecurity has an influence on Turnover Intention, job satisfaction and Job Insecurity has an influence on Turnover Intention.